2017
DOI: 10.3847/1538-4357/aa6af9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Backgrounds at Cosmic Dawn: X-Rays from Compact Binaries

Abstract: We compute the expected X-ray diffuse background and radiative feedback on the intergalactic medium (IGM) from X-ray binaries prior and during the epoch of reionization. The cosmic evolution of compact binaries is followed using a population synthesis technique that treats separately neutron stars and black hole binaries in different spectral states and is calibrated to reproduce the observed X-ray properties of galaxies at z ∼ < 4. Together with an updated empirical determination of the cosmic history of star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
403
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 354 publications
(423 citation statements)
references
References 122 publications
(171 reference statements)
20
403
0
Order By: Relevance
“…In the case of a galaxydominated reionization scenario, however, X-rays from compact binaries are expected to keep the electron fraction of the IGM between H II cavities below 1 percent (Madau & Fragos 2017). (12) and (13), and writing the total average opacity as κ ν ≡ (dτ /dz)|dz/cdt|, one then recovers Equation (14).…”
mentioning
confidence: 85%
“…In the case of a galaxydominated reionization scenario, however, X-rays from compact binaries are expected to keep the electron fraction of the IGM between H II cavities below 1 percent (Madau & Fragos 2017). (12) and (13), and writing the total average opacity as κ ν ≡ (dτ /dz)|dz/cdt|, one then recovers Equation (14).…”
mentioning
confidence: 85%
“…Supermassive black holes at the centers of galaxies shape their hosts through their powerful outflows (Fabian 2012), and their smaller cousins, black hole binaries (BHBs), may have played an important role during the epoch of ionization (e.g., Madau & Fragos 2017). Accretion processes in supermassive black holes are, however, hard to study because of their long variability timescale and large distances, which result in low fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Any strong accretion onto these massive Pop III seed BHs would lead to X-ray radiation at high redshifts (Kuhlen & Madau 2005;Alvarez et al 2009;Tanaka et al 2012;Visbal et al 2012). X-rays from Pop III binaries have been suggested to produce a pre-heated IGM (e.g., Mirabel et al 2011;Haiman 2011;Visbal et al 2012;Mesinger et al 2013;Madau & Fragos 2016), and to partially ionize the IGM in large volumes (e.g., Ostriker & Gnedin 1996;Pritchard & Furlanetto 2007). Xu et al (2014) showed that Pop III binaries might be the dominant X-ray sources at high redshifts and discussed how the IGM might be heated locally by hundred eV photons and globally by the X-ray background from keV photons.…”
mentioning
confidence: 99%